The Idea of The Muslim World, A Global Intellectual History - Maulana, Moch Dimas (Universitas Islam Internasional Indonesia, 2023)
The Idea of The Muslim World, A Global Intellectual History | Cemil Aydin | London: Harvard University Press, 2017. The notion of